2002
DOI: 10.1017/s1355838202022033
|View full text |Cite
|
Sign up to set email alerts
|

How Slu7 and Prp18 cooperate in the second step of yeast pre-mRNA splicing

Abstract: Slu7 and Prp18 act in concert during the second step of yeast pre-mRNA splicing. Here we show that the 382-amino-acid Slu7 protein contains two functionally important domains: a zinc knuckle (122CRNCGEAGHKEKDC135) and a Prp18-interaction domain (215EIELMKLELY224). Alanine cluster mutations of 215EIE217 and 221LELY224 abrogated Slu7 binding to Prp18 in a two-hybrid assay and in vitro, and elicited temperature-sensitive growth phenotypes in vivo. Yet, the mutations had no impact on Slu7 function in pre-mRNA spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
125
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(143 citation statements)
references
References 30 publications
17
125
0
1
Order By: Relevance
“…The interaction between Prp18 and Slu7 appears to be important for the proper function of both proteins+ Mutant Prp18s that fail to interact with Slu7 are invariably temperature sensitive+ These mutations can be suppressed to a similar extent by overexpression of Slu7 or by overexpression of the mutant prp18+ These (Horowitz & Abelson, 1993a;Brys & Schwer, 1996;Zhang & Schwer, 1997), but the possibility that Prp18 and Slu7 form a stable complex outside the spliceosome is not excluded by our results+ Our interpretation of the interactions of Prp18 and Slu7 is consistent with the recent work of James et al+ (2002), who studied the binding of Slu7 and Prp18 to the spliceosome in vitro+…”
Section: Interaction Of Prp18 With Slu7supporting
confidence: 85%
“…The interaction between Prp18 and Slu7 appears to be important for the proper function of both proteins+ Mutant Prp18s that fail to interact with Slu7 are invariably temperature sensitive+ These mutations can be suppressed to a similar extent by overexpression of Slu7 or by overexpression of the mutant prp18+ These (Horowitz & Abelson, 1993a;Brys & Schwer, 1996;Zhang & Schwer, 1997), but the possibility that Prp18 and Slu7 form a stable complex outside the spliceosome is not excluded by our results+ Our interpretation of the interactions of Prp18 and Slu7 is consistent with the recent work of James et al+ (2002), who studied the binding of Slu7 and Prp18 to the spliceosome in vitro+…”
Section: Interaction Of Prp18 With Slu7supporting
confidence: 85%
“…The strong association between Prp18 and Slu7 aids their spliceosome assembly (55). Our prior studies suggested weak or no interactions between fission yeast SpPrp18 and SpSlu7 (22).…”
Section: Discussionmentioning
confidence: 83%
“…After the first step of splicing, ATP hydrolysis by Prp16 leads to protection of the 3Ј splice site (7). We think that the ATP hydrolysis activates the spliceosome, permitting binding of Slu7, Prp18, and Prp22, and that this second-step spliceosome selects the 3Ј splice site and carries out the reaction (similar to the scheme of (9,10)). This model has a single kinetic step for identifying the 3Ј splice site and carrying out the reaction.…”
Section: Discussionmentioning
confidence: 94%
“…After the first transesterification, the RNA helicase Prp16 rearranges the spliceosome (7). Prp18, Slu7, and Prp22 join the spliceosome, which then rapidly ligates the exons (8)(9)(10). The U2, U5, and U6 snRNAs and the Prp8 protein, which are required for the first step of splicing, also participate directly in the second step (11,12).…”
mentioning
confidence: 99%